INFERIORITAS PEREMPUAN DALAM BAHASA IKLAN BANNER SAFETY RIDING - Patria, Fedi Bhakti (Jurnal Pena Indonesia, 2015)
Women are still often imaged positively by the authorities in the public sphere. This can be seen from some of the elements contained in the images, including in the text "Dear Sweet Wife / Mother wearing the left lane" on banner safety riding ads. The prominence of the term 'WIFE' and the term 'MOM' instead shows the passive position of women who are only positioned as 'silent' subjects to wait for their partner to return. But in this case, the rules of traffic order become the representation of the symbolic phallus. This study uses a qualitative method which in the study of cultural studies is described by Paul Willis as a model of reflexive methodology, where the emphasis lies in theoretical awareness and interest, to reach the depth of 'reality'. The results emphasize that the image of women remains served as a passive subject and tend to be obedient to all transcendent rules. So, it is not excessive if in the end, this image also represents an inferiority in women. However, it really directs, herds, and encourages its viewers to always bring their own narcissistic desires. The woman in the image has been mythical, and soon she becomes part of the banality in the spaces of society.